Fiqh Zakat: Pemerataan pembagian zakat kepada ashnaf sesuai syariat islam dalam perspektif Imam Syafi’i serta implikasi hukum dan problematikanya di era kontemporer - Faradila, Dinda Silvy (Maliki Interdisciplinary Journal, 2025)
The research examines the fiqh of zakat which focuses on the equitable distribution to the eight Ashnaf according to Imam Syafi’i. Zakat has an important role as a form of economic equality in society. Viewed from the Syafi’i madzhab, the distribution of zakat must be evenly distributed according to its target. This research analyses Imam Syafi’i’s argumentation and its legal implications in the application of fiqh zakat in the contemporary era. As we can see, nowadays there are many problems that arise so that the effectiveness of the goal of equal distribution of zakat is disrupted. Problems such as the priority of certain Ashnaf, efficiency in distribution require flexibility in implementing fiqh zakat that remains in accordance with Islamic shari’at.